Modelling SME e-commerce with IMAES (2019)
Purpose: There are several studies about the adoption of e-commerce for small-to-medium enterprises (SMEs) that separately, and in a dispersed manner, examine different theoretical approaches. The purpose of this paper is to unify a set of variables to form an integrated model of measurement of the adoption of e-commerce for SMEs. Design/methodology/discussion: Based on an extensive review of empirical studies focused on the adoption of e-commerce in SMEs, a grouped and integrated model of e-commerce among SMEs was constructed. It was built upon the methodology of psychometrics and was subsequently statistically tested for reliability and validity. A broad study has not been carried out. Thus, the small sample size does not allow the estimation of this model’s predictability. Findings: This paper proposes a final model, comprising 14 variables (82 items), grouping the significant effects of e-commerce adoption. Originality/value: This tool is feasible, offering an initial model enabling detailed examination of variables affecting the adoption of e-commerce in SMEs. It contributes significantly to the development of this line of research. © 2018, Emerald Publishing Limited.